The effect of using anaerobic ability exercises with suggested intensity on some physical and functional variables among young handball players - Kadhim, Mohammed Mahmood; HAMDAN, RAAD KHANJAR (International Journal of Psychosocial Rehabilitation, 2020)
The research community was determined and they represent deliberate players in the Karkh Sports Club handball, who are aged between (15-19 years) totaling 14 players, to represent 82% of the research community, divided into two experimental unequal. The researchers used the experimental method for its suitability and the nature of the research. The training curriculum was implemented with the suggested stresses, as the first group uses intensity between (50%- 65%) and the second group (65%- 80%) for period of (8) weeks, at two units per week. After completing the training curriculum and obtaining the data, it was processed statistically using the statistical program (SPSS). The research aimed to: Detecting the significance of the differences between the pretest and the post test of the two experimental groups in the physical and functional variables, to reveal the significance of the differences in the post test between the two experimental groups in the physical and functional variables. The following conclusions were reached: Affected anaerobic capacity training intensity proposed (50%- 65 %) in the development of maximum power and the two men and the explosive power of two distinctive power to speed and the two men. Anaerobic training at the suggested intensity (65%- 80%) affected the development of maximum strength in the arms, explosive strength of the arms and legs, and the characteristic velocity of the two legs. The training methodology of the first experimental group, which used intensity (50%- 65%), had an effect on the maximum strength of the two men better than the second group, which used intensity (65%- 80%). anaerobic exercises affected the ability of the proposed intensity on the low pulse rate for both groups.